Why Games Are Good For Business How to Leverage the Power of Serious Games, Gamification and Simulations - Routledge, Helen; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
By tapping into the same psychology that keeps gamers glued to Minecraft or World of Warcraft, innovative organizations are creating their own engaging and flexible learning experiences. They're called Serious Games. This is a practical toolkit for those who want to learn about more serious games and how to apply them in the workplace.
Keywords: Business; Management; Leadership; Organization; Planning; Personnel management; Manpower policy; Behavioral economics; Business and Management; Management; Organization; Human Resource Management; Human Resource Development; Behavioral/Experimental Economics; Business Strategy/Leadership.; Electronic books